Effects of gamma and electron-beam irradiation on the antioxidant potential of Melissa officinalis L. infusions - Pereira, Eliana (2014)
Gamma and electron beam irradiation are two processes authorized for food processing, characterized as technically and economically feasible procedures, and safe, with a powerful antimicrobial effect. These decontamination methods have advantages that are increasingly attracting the market and present a good alternative to other methods [1,2]. In this work, the effects of gamma irradiation and electron beam on antioxidant activity of Melissa officinalis L., were evaluated. Infusions were prepared from non-irradiated and irradiated samples (1 and 10 kGy), and their radical scavenging activity, reducing power and inhibition of lipid peroxidation were assessed. According to the results obtained, it was concluded that in samples exposed to gamma irradiation, the highest antioxidant potential was displayed by the infusions prepared from the samples irradiated at 1 kGy, as well as the highest concentration of phenols and flavonoids. Regarding the samples exposed to electron beam irradiation, the mentioned effects were not so evident and, in most of the cases, no changes were observed among non-irradiated and irradiated samples. Overall, irradiation might represent a suitable solution for M. officinalis postharvest treatment, since the use of irradiation did not interfere with its antioxidant properties, and gamma irradiation at 1 kGy even improved some of the antioxidant potential, preserving the bioactive compounds that confer health beneficial effects.